Recovering abundance : twelve practices for small-town leaders - Stanton-Henry, Andy (Fortress Press, 2022)
Recovering Abundance invites readers to join a movement of renewal for small towns and rural communities. Andy Stanton-Henry explores twelve civic-spiritual practices, rooted in Jesus's miracle among the multitude, demonstrating how it has been embodied in ordinary leaders and how it can be applied today.